2016
DOI: 10.1007/s11005-016-0917-8
|View full text |Cite
|
Sign up to set email alerts
|

A spectral isoperimetric inequality for cones

Abstract: In this note we investigate three-dimensional Schr\"odinger operators with $\delta$-interactions supported on $C^2$-smooth cones, both finite and infinite. Our main results concern a Faber-Krahn-type inequality for the principal eigenvalue of these operators. The proofs rely on the Birman-Schwinger principle and on the fact that circles are unique minimizers for a class of energy functionals. The main novel idea consists in the way of constructing test functions for the Birman-Schwinger principle.Comment: 13 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…1.3] in the setting of δ-interactions supported on conical surfaces. However, the technique employed here is significantly different from the one used in [EL17]. In the latter paper, the spectral problem was first reformulated as a boundary integral equation by means of the Birman-Schwinger-type principle.…”
Section: Resultsmentioning
confidence: 99%
“…1.3] in the setting of δ-interactions supported on conical surfaces. However, the technique employed here is significantly different from the one used in [EL17]. In the latter paper, the spectral problem was first reformulated as a boundary integral equation by means of the Birman-Schwinger-type principle.…”
Section: Resultsmentioning
confidence: 99%
“…, N (see [1,2,3,6] and Section 2 for basic definitions). The question of optimization of the principal eigenvalue of self-adjoint Schrödinger Hamiltonians with δ-type or point interactions attracted recently considerable attention especially in a quantum mechanics context [14,17,16,18,36]. This line of research was motivated by the isoperimetric problem posed in [14].…”
Section: Statement Of Problem Motivation and Related Studiesmentioning
confidence: 99%
“…The result of Theorem 5 can be viewed as a kind of isoperimetric inequality: among the conical surfaces with smooth cross-sections of fixed length l ≤ 2π, the circular cones give the highest rate for the accumulation of discrete eigenvalues to the bottom of the essential spectrum for both A S and B S . Remark that the first eigenvalue of B S is also maximized by the circular cones, see [13]. …”
Section: Theorem 2 (Dirichlet Laplacian In a Conical Layer) There Holdsmentioning
confidence: 99%
“…The paper [4] studied general conical surfaces and an expression for the bottom of the essential spectrum of B S was obtained. The paper [13] contains first results on the discrete spectrum of the operator B S for conical surfaces S with arbitrary smooth cross-sections, and the authors showed that there is at least one eigenvalue below the essential spectrum. They also posed an open question on whether or not the discrete spectrum is always infinite.…”
mentioning
confidence: 99%